(3cJGH GddGeGJs - (3CHh LYaQ Hf ESeGYjd Hf YHO Gddg GdfMGSs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje EYde QMec Gddg Cf dGe GdbSe efUhHI ai PGJgG hJCJi ai BNQ GdcdGe Hfhf eTOOI hEfeG SejJ dGe GdbSe dCf Gdjejf jMSf ajgG s
(3BNQgG (B:s
(3hcPdc dfKHJ Hg aDGOc hcPdc djZaQ dc Gddg eG JbOe ef PfHc heG JCNQ eYfGg dci jZaQ Gddg dc agPG dGe ci heG CTHggG GfJgi HMeO Gddg hMSf Yhfg hJhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs